Discussion on Issues Related to Drug Application in Cosmetic Industry: A Case Study of the Olmedine Incident - Haifeng YAO; Hua HOU; Zhaohui ZHAI (Yixue yu zhexue, 2025)
Olmedine was an early medical soft tissue injection material introduced in China. It has been widely used in breast augmentation, facial fillers, buttock augmentation and other plastic surgeries. In 2006, Olmedine was banned because of a large number of adverse events and complications after injection. The Olmedine incident was a major public safety crisis, exposing the loopholes in the approval process, supervision means and professional ethics of the cosmetic medicine industry. Despite the ban, unapproved injection materials and illegal procedures still exist in China's cosmetic industry, posing significant safety risks. Using the Olmedine incident as a case study, this paper reflects on the safety issues of injection materials in China's cosmetic industry and explores improvements in industry ethics and governance. The goal is to promote the standardized development of the cosmetic industry and protect consumer health and rights.